PENGARUH LARUTAN ASAM TERHADAP FLUKTUASI PH HIDROPONIK - Ratna Zulfarosda; Retno Tri Purnamasari (Universitas Tribhuwana Tunggadewi, 2022)
Hydroponics uses water as a growing medium and a source of nutrients for the plant. Water conditions suitable for plant growth have a pH of 5.6-6.5. Water conditions in Pasuruan City tend to be alkaline with pH 8. It is necessary to give an acid solution to reduce the pH value. This research aimed to study the effect of nitric acid, phosphoric acid, and sulfuric acid on fluctuation in the pH of hydroponics. The study used a Randomized Block Design with nine treatments: Kebonsari Village water + nitric acid; Kebonsari Village water + phosphoric acid; Kebonsari Village water + sulfuric acid; Bugul Kidul Village water + nitric acid; Bugul Kidul Village water + phosphoric acid; Bugul Kidul Village water + sulfuric acid; PDAM water + nitric acid; PDAM water + phosphoric acid; and PDAM water + sulfuric acid. The results showed that the phosphoric acid solution was able to maintain the pH in the optimal range of 6,8 – 7,1 for all types of water, more stable than nitric acid and sulfuric acid solutions. Plants cultivated with PDAM water with phosphoric acid solution showed high leaf chlorophyll content (48,480 mg/L), leaf Nitrogen (4,38%), and plant weight (1.807,00 g).